Determinants of macroscopic anal cancer and precancerous lesions in 1206 HIV‐infected screened patients. (October 2016) - Abramowitz, L.; Benabderrahmane, D.; Walker, F.; Yazdapanah, Y.; Yéni, P.; Rioux, C.; Bouscarat, F.; Lafferre, E.; Mentré, F.; Duval, X.
Abstract: Aim: Anal screening is recommended in HIV‐positive patients, especially men who have sex with men (MSM), due to an increased incidence of anal cancer. The optimal screening methods are not generally agreed. Method: Screening for anal lesions by anorectal examination, including anoscopy, was offered to HIV‐positive outpatients in a tertiary care university hospital regardless of gender or sexual orientation. Results: Among the 1206 screened patients (701 MSM, 247 heterosexual men, 258 women), 311 (26%) had histologically proven lesions related to human papilloma virus (HPV) (34% MSM, 14% heterosexual men, 14% women); 123 (10%) had low‐grade dysplasia and 70 (6%) high‐grade dysplasia. Seven anal cancers were also diagnosed. Determinants of any lesion were age < 45 years [OR = 1.56 (95% CI, 1.16–2.11)], a CD4 count of < 200/mm 3 [OR = 2.54 (1.71–3.78)], receptive anal intercourse [OR =3.03 (2.06–4.47)], sub‐Saharan African origin [OR = 0.53 (0.33–0.85)], and history of HPV‐related lesion [OR = 1.84 (1.35–2.51)]. These determinants were similar for all different grades of dysplasia. In patient subgroup analysis, receptive anal intercourse, the CD4 cell count and a history of HPV lesions were determinants of HPV‐positivity in all patients, whereas age was only a determinant in men. Conclusion: Anoscopy is an alternative method for anal screening in an HIV‐positive population. This screening has to be compared with other tools in populations at high risk of anal cancer.